Superior outcomes for military ankylosing spondylitis patients treated with anti-TNF. Issue 4 (22nd January 2014) - Rees, Jonathan D; Bennett, A N; Harris, D; Jones, T
Abstract : Objectives: The British military has a cohort of patients with ankylosing spondylitis (AS) characterised by young age and short disease duration. Many of the most severely affected AS patients have been treated since 2005 at Headley Court with anti-tumour necrosis factor (anti-TNF) therapy in accordance with National Institute of Health and Care Excellence guidance. We wanted to prospectively determine both the safety and efficacy of this new treatment in our British military population and compare this with relevant civilian study outcome data. Methods: All AS patients commenced on anti-TNF therapy at Headley Court were prospectively monitored for treatment efficacy and side effects. Outcome measures used included the Bath Ankylosing Spondylitis Disease Activity Index. Our results were compared with a civilian comparison group (NHS) and relevant landmark clinical trial data. Results: Our patients were younger (mean age 34.7 years) and had a shorter duration (mean disease duration 6.9 years) than the civilian (NHS) comparison group. Our safety data were extremely benign with only two patients suffering minor side effects (local injection site reaction). Furthermore, our outcome data were superior to both NHS routine care and to landmark clinical studies. Discussion: Prior to this study, there were no data on military AS populations receiving anti-TNF therapy. The study confirms British military patients tolerate this therapy extremely well and receive greater benefit from this treatment than that seen in any published study to date. We believe that this confirms that young age and short disease duration are good prognostic factors in the treatment of AS with anti-TNF therapy.